MRI Study on the Effects of Platinum-based Chemotherapy on Brain Lateralization in Patients with Lung Cancer - Ping RONG; Ming LI; Shangwen YANG; Xiaoyan XIN; Wen YANG; Qianqian FENG; Wenqian CHEN; Renyuan LIU; Mei YAO (CT Lilun yu yingyong yanjiu)
This study aimed to investigate the impact of platinum-based chemotherapy on cerebral cortex thickness in patients with lung cancer, focusing on bilateral hemispheres and lateralization characteristics. Data from 191 participants who underwent head magnetic resonance imaging (MRI) with a 3D-T1WI sequence at Nanjing Drum Tower Hospital between January 2019 and June 2021 were retrospectively analyzed. The sample included 38 patients with lung cancer who were treated with platinum-based chemotherapy, 113 patients with lung cancer who did not receive any form of chemotherapy, and 40 healthy controls matched for age, sex, and educational level. Cortical thickness changes were compared among the three groups using a two-sample t-test to evaluate specific differences. Significant differences in the thicknesses of multiple cortical regions were observed between patients with lung cancer (both those who received and did not receive platinum-based chemotherapy) and healthy controls. Notably, patients with lung cancer who did not receive chemotherapy exhibited more pronounced differences in the anterior cingulate gyrus and superior temporal cortex in both hemispheres than the healthy control and chemotherapy groups. Additionally, in the healthy control group and patients with lung cancer receiving platinum-based chemotherapy, the thickness of the right inferior frontal gyrus decreased with age; however, this correlation was not observed in patients with lung cancer who did not receive chemotherapy. This study suggests that lung cancer may lead to cortical atrophy, particularly in patients who have not received platinum-based anticancer drugs. Furthermore, structural changes in the brain induced by disease exhibited a certain degree of lateralization.